The role of youth and scouting education in enhancing student character development - Hidayah, Eva Nur; Murdiono, Mukhamad; Wiratomo, Giri Harto; Hermawan, Dwi (Universitas Negeri Yogyakarta, 2023)
This study investigates the role of Youth and Scouting Education (PGMK) in strengthening student character and identifying the driving and inhibiting factors affecting this process. The research utilized a descriptive approach with a qualitative method, conducted at Universitas Negeri Semarang, focusing on outbound learning for PGMK subjects. The data collection techniques used in this research included interviews, observations, and documentation, while the validity of the data was tested through informant review, member check, and triangulation. Data analysis was conducted interactively by collecting, reducing, displaying, and drawing conclusions from the data. The study found that PGMK played a significant role in developing the soft and hard skills necessary to strengthen participants' character. However, this process was both encouraged and hindered by various factors such as the example of tutors, the curriculum design, the PGMK committee's commitment, stakeholder support, equalization of perceptions among participants, conducive learning situations, learning models, tutors' capacity building and competence, learning intensity and duration, internet connection, and the environment. These findings suggest the importance of considering these factors in designing and implementing effective character education programs for students.